1977 Painting 100 - Darjac (Wikimedia Commons, 2010)
Notice iconographique issue de Wikimedia Commons. Titre: 1977 Painting 100. French Paintings - Venus in the Clouds Denomination: 1 Forint
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures